2017
DOI: 10.1016/j.toxlet.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-oxide impairs pyruvate and fatty acid oxidation in cardiac mitochondria

Abstract: Increased plasma concentration of trimethylamine N-oxide (TMAO), a proatherogenic metabolite, has been linked to adverse cardiovascular outcomes; however, it remains unclear whether TMAO is a biomarker or whether it induces direct detrimental cardiovascular effects. Because altered cardiac energy metabolism and mitochondrial dysfunction play crucial roles in the development of cardiovascular diseases, we hypothesized that increased TMAO concentration may alter mitochondrial energy metabolism. The aim of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 45 publications
(66 reference statements)
0
70
0
1
Order By: Relevance
“…Although most studies in humans have focused on TMAO in coronary artery disease, TMAO has been shown to be increased in people with congestive heart failure (CHF) resulting from both ischemic and nonischemic heart disease . Results of 2 recent in vitro studies suggest that TMAO's nonvascular adverse effects on the heart could be the result of decreased cardiomyocyte contractility and intracellular calcium flux or impaired myocardial energy metabolism . Alternatively, increased TMAO may not be a cause of CV pathology but may be the result of inflammation associated with CV disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies in humans have focused on TMAO in coronary artery disease, TMAO has been shown to be increased in people with congestive heart failure (CHF) resulting from both ischemic and nonischemic heart disease . Results of 2 recent in vitro studies suggest that TMAO's nonvascular adverse effects on the heart could be the result of decreased cardiomyocyte contractility and intracellular calcium flux or impaired myocardial energy metabolism . Alternatively, increased TMAO may not be a cause of CV pathology but may be the result of inflammation associated with CV disease.…”
Section: Introductionmentioning
confidence: 99%
“…Defective or downregulated FMO3 can cause trimethylaminouria or “fish odor syndrome” . The exact mechanism by which TMA/TMAO exercises its influence is not exactly known, although there have been several suggestions: negative influence of TMAO on cholesterol efflux from foam cells ; influence of TMA/TMAO on FMO3, a key known regulator of cholesterol metabolism activity ; possible hypersensitization of platelets by TMAO ; and impairment of pyruvate and fatty acid oxidation in cardiac mitochondria . There is also some controversy about whether TMAO is actually a cause of atherosclerosis or merely a marker of it .…”
Section: Introductionmentioning
confidence: 99%
“…To assess the effect of voluntary exercise on WD-induced cardiac dysfunction and molecular mechanism, mice were randomly divided into four groups ( n = 10 for each group): (1) normal diet-sedentary (ND-SED), (2) western diet-sedentary (WD-SED), (3) western diet-voluntary exercise (WD-EXE), and (4) western diet-voluntary exercise with TMAO administration (WD-EXE-TMAO). Groups underwent simultaneous diet modification and voluntary exercise training with or without administration of TMAO (120 mg/kg) in drinking water (Makrecka-Kuka et al, 2017 ) for 8 weeks. The ND (Teklad LM-385, Harlan) contained 17% total fat, 0.8% saturated fat, and 0% sucrose, while WD (TD 88137, Harlan) had 42% total fat, 12.8% saturated fat, and 30% sucrose.…”
Section: Methodsmentioning
confidence: 99%